2021
DOI: 10.3389/fonc.2021.739103
|View full text |Cite
|
Sign up to set email alerts
|

Residual Volume of Lymph Nodes During Chemoradiotherapy Based Nomogram to Predict Survival of Nasopharyngeal Carcinoma Patient Receiving Induction Chemotherapy

Abstract: PurposeTo accurately stratify nasopharyngeal carcinoma (NPC) patients who were benefit from induction chemotherapy (IC) followed by chemoradiotherapy (CCRT), we established residual volume of lymph nodes during chemoradiotherapy based nomogram to predict survival for NPC patients.MethodsCox regression analysis were used to evaluate predictive effects of tumor volume parameters. Multivariate Cox regression analysis was used to identify the prognostic factors, and nomogram models were developed to predict surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…This result suggested that increasing treatment intensity might improve prognosis for elder patient with good status. Our previous study and published studies con rmed that primary tumor volume negatively affected prognosis of NPC [15,19,20]. In this study, IC followed by CCRT signi cantly decreased death risk for patient with primary tumor volume ≦ 52.6cc in subgroup analysis, indicating small primary tumor volume might be easier to achieve better survival bene t from IC followed by CCRT in T3-4 patient.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This result suggested that increasing treatment intensity might improve prognosis for elder patient with good status. Our previous study and published studies con rmed that primary tumor volume negatively affected prognosis of NPC [15,19,20]. In this study, IC followed by CCRT signi cantly decreased death risk for patient with primary tumor volume ≦ 52.6cc in subgroup analysis, indicating small primary tumor volume might be easier to achieve better survival bene t from IC followed by CCRT in T3-4 patient.…”
Section: Discussionsupporting
confidence: 64%
“…Many studies identi ed age was a prognostic factor for poor OS of NPC [15,17,18]. In this study, IC followed by CCRT could signi cantly improve OS in patients with age > 45 year according to subgroup analysis.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Such a phenomenon might be associated with individual chemo-and radiosensitivity. 12,21,22 In 2019, Liang et al 23 reported that patients with non-CR of the PT or metastatic lymph nodes at the end of RT had a worse prognosis than those with CR. Unlike their findings, we found that PT regression, but not CLNs regression at mid-RT, plays a critical role in predicting DFS and OS of patients with LA-NPC (Figures 1C,D and 2C,D).…”
Section: Discussionmentioning
confidence: 99%
“…The current study confirmed the data of previous studies that tumor response has prognostic value for patients with LANPC. Although the tumor regressions during and after radiotherapy were also demonstrated to predict clinical outcomes, and to a certain extent, could represent radiation sensitivity, [27][28][29] early assessment before the implement of radiotherapy can help guide clinicians in choosing more individualized treatment regime in a timely manner.…”
Section: Discussionmentioning
confidence: 99%